Analisis Biaya Obat Unit Rawat Jalan pada Rumah Sakit Badan Layanan Umum (BLU)/ Badan Layanan Umum Daerah (BLUD) di Indonesia - Suharmiati, Suharmiati; Handayani, Lestari; Roosihermiatie, Betty (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2019)
Drugs expenditure is the highest proportion in health services budget. financing for health services in National Universal Health Coverage era is carried out by BPJS payed to referral health facilities namely hospitals. The medicine cost at public service agency/District or Province public service agency is unknown certaintly. This descriptive study was advanced analyzes of the secondary data of 84 hospitals from health financing research in the year of 2016. The result showed that there were problems of drug availability in class B 94,6%, C 78,9% and A 77,8%. The highest proportion of generic drugs cost to total drug cost is class C hospital, followed by B class and A class hospitals i.e 40,57%, 37,83% dan 23,74% respectively. The cost of non generic drug compared to generic drugs at A, B and C class is 2,22 times, 1,15 times and 0,86 times respectively. The highest cost of generic drug is in outpatient specialist services in all class of hospitals. The cost of the drugs was increasing higher as well as the hospital class. Conclusion: The non generic drugs cost dominated in A and B class hospital while C class was generic drug cost. Generic drug use policy should be socialyzed by government and to be considered by management in order to be able to carried out cost efficiency.